DETERMINANTS OF FOREIGN CURRENCY HEDGING AND IT’S IMPACT ON FIRM VALUE - Amalia Hasna Fadhila; Riwi Sumantyo (MESP–FEB UNS, 2023)
Hedging through derivative instruments is a risk management action to reduce losses due to foreign exchange exposure. This research aims to examine the influence of liquidity, company size, leverage, growth opportunity, financial distress, profitability on company hedging decisions and to find out whether hedging activities have an effect on company value. The research sample consisted of 39 companies in the basic industry and chemical goods sector listed on the Indonesia Stock Exchange in 2014-2018. This research uses two stages of testing to analyze the data. The first stage uses logistic regression to test decision determinants hedging company. The second stage uses testing Independent Sample T-Test to determine the impact of activities hedging on company value and knowing which groups of companies have superior value. The research results show that leverage, company size and growth opportunity have a positive effect on the probability of a company's hedging decisions. Meanwhile, financial distress, liquidity and profitability have a negative effect on the probability of a company's hedging decisions. There is a significant difference in the average value between companies that carry out hedging activities and companies that do not carry out hedging activities.